Prediction of Coronary Artery Disease by Erectile Function Status: Evidence‐Based Data. Issue 2 (11th June 2013) - Jackson, Graham
Abstract: The link between erectile dysfunction (ED) and cardiovascular disease (CVD) has been established as a result of individual studies and meta‐analyses. ED predicts CVD, coronary disease, myocardial infarction, heart failure, and increased mortality. ED may occur on average 2–5 years before a CVD event and act as a marker for early asymptomatic vascular, and especially coronary artery, disease. Seventy percent of men with known CVD also have ED that identifies a further increased CVD event risk when compared with men with normal erections. Importantly, those at highest risk are men with ED aged 30–60 years and diabetics where CVD detection and prevention need the most focus. A question on ED should be incorporated in all CVD risk calculators, and when risk is identified, action to reduce risk should be aggressively initiated and monitored.Jackson G. Prediction of coronary artery disease by erectile function status: Evidence‐based data. Sex Med Rev **;**:**–**.